A battery and an electric device
Patent Information
- Application Number
- CN202510425661.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]针对现有电池中电池安全性有待提高的问题,本发明提供了一种电池及用电装置
[0019]In this invention, by selecting a solvent system with a high boiling point and a moderate dielectric constant, the thermal stability and antioxidant capacity of the electrolyte can be effectively improved, reducing the risk of high-temperature volatilization and decomposition. By controlling the solvation structure to preferentially form anion-rich Li⁺ solvation sheath, the activity of free solvent can be reduced, inhibiting its reduction and gas generation and dendrite growth at the negative electrode interface. A moderate dielectric environment balances the dissociation and ion migration efficiency of lithium salt, avoiding excessive viscosity from losing conductivity. Furthermore, by introducing additives, the flash point of the electrolyte can be synergistically improved and the combustion chain reaction can be blocked through physical dilution effect and chemical free radical capture mechanism. The synergistic effect of fluorinated ethers and phosphate esters can form a dense passivation film, inhibiting the violent exothermic reaction between the electrolyte and the electrode. Boron-containing additives further improve the safety of the system by catalytically decomposing combustible gases. By depositing an SEI layer and/or a lithium alloy layer on the surface of the negative electrode active material layer, direct contact between metallic lithium and the electrolyte/electrolyte can be effectively avoided. This facilitates the uniform deposition and diffusion of lithium ions within the lithium metal negative electrode, effectively mitigating issues such as SEI film thickening and continuous lithium dendrite growth, thereby enhancing the safety performance of the battery cell. The combined effects of solvents, additives, and the positive and negative electrode plates further significantly improve the safety performance of the battery cell.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, specifically relating to a battery and an electrical device. Background Technology
[0002] With the rapid development of electric vehicles and mobile electronic devices, the demand for rechargeable batteries is increasing, particularly regarding energy density, safety, and cycle performance. Energy density and cycle performance are crucial parameters for evaluating rechargeable battery performance. Lithium metal has the lowest relative atomic mass (6.94) and the lowest standard electrode potential (-3.045V) among all metallic elements, with a theoretical specific capacity of 3860mAh / g. Therefore, using lithium metal as the negative electrode, combined with high-energy-density positive electrode materials, can significantly improve the battery's energy density (>400Wh / kg) and operating voltage (>4.5V). Batteries typically use lithium-coated copper strips as the negative electrode; however, lithium metal is highly reactive and readily reacts with the electrolyte, forming dendrites. These dendrites can grow and contact the positive electrode, causing a short circuit and posing a safety hazard. Summary of the Invention
[0003] To address the issue of insufficient battery safety in existing batteries, this invention provides a battery and an electrical device.
[0004] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: In a first aspect, the present invention provides a battery comprising an electrolyte, a positive electrode, and a negative electrode, wherein the electrolyte comprises an additive and a solvent, and the additive comprises one or more of silanes and their derivatives, fluorinated compounds, phosphazene compounds, ethyl hexafluorophosphate, propyl pentafluorophosphate, tris(trimethylsilane) phosphate, trifuranyl phosphite, and boron-containing compounds. The solvent includes one or more of carbonate solvents, ether solvents, phosphate solvents, fluorinated solvents, and ionic liquids; The positive electrode sheet includes a positive current collector and a positive active material layer, wherein the positive active material layer is disposed on at least one surface of the positive current collector; The negative electrode sheet includes a negative current collector, a negative active material layer, and a first functional layer. The negative active material layer includes metallic lithium or a lithium alloy and is disposed on at least one surface of the negative current collector. The first functional layer is disposed on the side of the negative active material layer opposite to the negative current collector and includes an SEI layer and / or a lithium alloy layer.
[0005] Optionally, the silane and its derivatives include one or more of vinyltrimethylsilane, tetravinylsilane, dimethyldimethoxysilane, and trimethoxyphenylsilane; And / or, the fluorinated compound includes perfluorohexanone; And / or, the phosphazene compounds include pentafluoroethoxycyclotriphosphazene; And / or, the boron-containing compound includes one or more of tris(pentafluorophenyl)borane, triethyl borate, and tris(trimethylsilyl)borate.
[0006] Optionally, the additive further includes one or more of 1,3-propenesulfonate lactone, lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorooxalate borate, and lithium difluorobis(oxalate) phosphate.
[0007] Optionally, the mass content of the additive in the electrolyte is 0.5% to 15%, and the mass content of the solvent in the electrolyte is 15% to 90%.
[0008] Optionally, both the positive current collector and the negative current collector include metal foil and / or composite current collector; the composite current collector includes a base film and conductive layers disposed on both sides of the base film; The positive electrode and the negative electrode further include a second functional layer, which is disposed on at least one surface of the metal foil; and / or, the second functional layer is disposed between the base film and the conductive layer.
[0009] Optionally, the second functional layer includes a strength layer and / or a security layer; The strength layer includes an aluminum oxide layer; the safety layer includes one or more of barium titanate, lead titanate, and polymethyl methacrylate.
[0010] Optionally, an underlayer is provided between the base film and the second functional layer, the underlayer comprising one or more elements selected from iron, silicon, magnesium, copper, manganese, zinc, lead, titanium, chromium, aluminum, and nickel.
[0011] Optionally, the positive electrode sheet further includes an electronic insulating protective layer, which is disposed at the edge of the positive current collector, and the side of the electronic insulating protective layer near the positive active material layer intersects with or covers part of the positive active material layer.
[0012] Optionally, the electronic insulating protective layer comprises one or more of the following: polyvinylidene fluoride and its modified forms, polyimide and its modified forms, polytetrafluoroethylene and its modified forms, para-aramid and its modified forms, meta-aramid and its modified forms, alumina, boehmite, zinc oxide, zirconium dioxide, titanium dioxide, and barium sulfate.
[0013] Optionally, the SEI layer includes one or more of a lithium compound layer, a carbon material layer, and a polymer layer; The lithium alloy layer comprises an alloy formed of metallic lithium and one or more of the following: gold, indium, magnesium, zinc, chromium, nickel, molybdenum, tungsten, vanadium, titanium, niobium, zirconium, cobalt, manganese, aluminum, copper, boron, silver, tin, silicon, carbon, phosphorus, and bismuth.
[0014] Optionally, the lithium compound layer comprises one or more compounds formed with metallic lithium, selected from fluorine, oxygen, sulfur, nitrogen, carbon, and phosphorus; The carbon material layer includes one or more of graphite, soft carbon, hard carbon, carbon black, amorphous carbon, graphene, and carbon nanotubes. The polymer layer comprises one or more of the following: polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polydimethylsiloxane, polyacrylic acid, metal-organic framework, covalent organic framework, polyether, polyester, polyurethane, polycarbonate, polyacrylate, polyacrylamide, polysiloxane, polyimide, self-porous polymer, and supramolecular polymer.
[0015] Optionally, the electrolyte further includes a lithium salt, wherein the concentration of the lithium salt is 0.5~5M.
[0016] Optionally, the battery further includes a separator, which is a polymer porous base membrane or a coated separator, wherein the coated separator includes a polymer porous base membrane and a functional coating disposed on at least one side of the polymer porous base membrane; The polymer porous base membrane includes at least one of polyethylene and polypropylene; the functional coating includes one or more of a high-temperature resistant compound, a polymer binder, a thickener, and a wetting agent.
[0017] Optionally, the high-temperature resistant compound includes one or more of the following: oxide solid electrolyte, halide solid electrolyte, sulfide solid electrolyte, alumina, boehmite, zinc oxide, zirconium dioxide, titanium dioxide, barium sulfate, polyvinylidene fluoride and its copolymers, aramid, polymethyl methacrylate and its modifiers.
[0018] Secondly, the present invention also provides an electrical device including the battery described above.
[0019] In this invention, by selecting a solvent system with a high boiling point and a moderate dielectric constant, the thermal stability and antioxidant capacity of the electrolyte can be effectively improved, reducing the risk of high-temperature volatilization and decomposition. By controlling the solvation structure to preferentially form anion-rich Li⁺ solvation sheath, the activity of free solvent can be reduced, inhibiting its reduction and gas generation and dendrite growth at the negative electrode interface. A moderate dielectric environment balances the dissociation and ion migration efficiency of lithium salt, avoiding excessive viscosity from losing conductivity. Furthermore, by introducing additives, the flash point of the electrolyte can be synergistically improved and the combustion chain reaction can be blocked through physical dilution effect and chemical free radical capture mechanism. The synergistic effect of fluorinated ethers and phosphate esters can form a dense passivation film, inhibiting the violent exothermic reaction between the electrolyte and the electrode. Boron-containing additives further improve the safety of the system by catalytically decomposing combustible gases. By depositing an SEI layer and / or a lithium alloy layer on the surface of the negative electrode active material layer, direct contact between metallic lithium and the electrolyte / electrolyte can be effectively avoided. This facilitates the uniform deposition and diffusion of lithium ions within the lithium metal negative electrode, effectively mitigating issues such as SEI film thickening and continuous lithium dendrite growth, thereby enhancing the safety performance of the battery cell. The combined effects of solvents, additives, and the positive and negative electrode plates further significantly improve the safety performance of the battery cell. Detailed Implementation
[0020] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0021] An embodiment of the present invention provides a battery comprising an electrolyte, a positive electrode, and a negative electrode. The electrolyte comprises additives and a solvent. The additives include one or more of silanes and their derivatives, fluorinated compounds, phosphazene compounds, ethyl hexafluorophosphate (FEP), propyl pentafluorophosphate (FPP), tri(trimethylsilane) phosphate (TMSP), trifuranyl phosphite (FuP), and boron-containing compounds. Specifically, one or more of ethyl hexafluorophosphate (FEP), propyl pentafluorophosphate (FPP), tri(trimethylsilane) phosphate (TMSP), and trifuranyl phosphite (FuP) decompose to generate phosphates, forming a barrier layer to inhibit combustion.
[0022] The solvent includes one or more of carbonate solvents, ether solvents, phosphate solvents, fluorinated solvents, and ionic liquids; The positive electrode sheet includes a positive current collector and a positive active material layer, wherein the positive active material layer is disposed on at least one surface of the positive current collector; The negative electrode sheet includes a negative current collector, a negative active material layer, and a first functional layer. The negative active material layer includes metallic lithium or a lithium alloy and is disposed on at least one surface of the negative current collector. The first functional layer is disposed on the side of the negative active material layer opposite to the negative current collector and includes an SEI (solid electrolyte interphase) layer and / or a lithium alloy layer.
[0023] In this embodiment, by selecting a solvent system with a high boiling point and a moderate dielectric constant, the thermal stability and antioxidant capacity of the electrolyte can be effectively improved, reducing the risk of high-temperature volatilization and decomposition. By controlling the solvation structure to preferentially form anion-rich Li⁺ solvation sheath, the activity of the free solvent can be reduced, inhibiting its reduction and gas generation and dendrite growth at the negative electrode interface. The moderate dielectric environment balances the dissociation and ion migration efficiency of lithium salt, avoiding excessive viscosity from losing conductivity. Further, by introducing additives, the flash point of the electrolyte can be synergistically improved and the combustion chain reaction can be blocked through physical dilution effect and chemical free radical capture mechanism. The synergistic effect of fluorinated ethers and phosphate esters can form a dense passivation film, inhibiting the violent exothermic reaction between the electrolyte and the electrode. The boron-containing additive further improves the safety of the system by catalytically decomposing combustible gases. By depositing an SEI layer and / or a lithium alloy layer on the surface of the negative electrode active material layer, direct contact between metallic lithium and the electrolyte / electrolyte can be effectively avoided. This facilitates the uniform deposition and diffusion of lithium ions within the lithium metal negative electrode, effectively mitigating issues such as SEI film thickening and continuous lithium dendrite growth, thereby enhancing the safety performance of the battery cell. The combined effects of solvents, additives, and the positive and negative electrode plates further significantly improve the safety performance of the battery cell.
[0024] By using the above-mentioned solvents and additives in combination, the thermal decomposition temperature of the electrolyte is 180℃-300℃, and the self-extinguishing time is 0-5s / g.
[0025] In one embodiment, the silane and its derivatives include one or more of vinyltrimethylsilane (VTMS), tetravinylsilane (TVS), dimethyldimethoxysilane (DMMS), and trimethoxyphenylsilane (TMPS); by introducing silane and its derivatives, a dense protective film is formed on the positive and negative electrode surfaces, effectively isolating the electrolyte from direct contact with the electrodes, reducing solvent decomposition, and thus suppressing battery gas generation.
[0026] The fluorinated compounds include perfluorohexanone (PFHK).
[0027] The phosphazene compounds include pentafluoroethoxycyclotriphosphazene (PFPN); by adding perfluorohexanone or pentafluoroethoxycyclotriphosphazene, the chain reaction of free radicals in the electrolyte is interrupted, thereby achieving a flame retardant effect.
[0028] The boron-containing compound includes one or more of tris(pentafluorophenyl)borane (TPFPB), triethyl borate (TEB), and tris(trimethylsilyl)borate (TMSB). The boron-containing compound inhibits combustion and stabilizes the electrode interface by forming a borate protective layer.
[0029] In one embodiment, the additive further includes one or more of 1,3-propenesulfonate lactone (1,3-PS), lithium tetrafluoroborate, lithium difluorophosphate (LiDFP), lithium difluorooxalate borate (LiDFOB), and lithium difluorobis(oxalate) phosphate (LiDFOP). The addition of these additives facilitates the formation of a stable interfacial film on the electrode surface and improves the thermal stability of the electrolyte.
[0030] Furthermore, carbonate solvents include one or more of ethylene carbonate (EC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC), bis(2,2,2-trifluoroethyl) carbonate (DFEC), and methyl ethyl carbonate (EMC).
[0031] The ether solvents include one or more of the following: dimethyl glycol ether (DME), diethyl glycol ether (DEE), 1,3-dioxane (DOL), tetrahydrofuran (THF), diethylene glycol dimethyl ether (DGM), triethylene glycol dimethyl ether (T3GM), and tetraethylene glycol dimethyl ether (T4GM).
[0032] Phosphate ester solvents include one or more of trimethyl phosphate (TMP), triethyl phosphate (TEP), trimethyl phosphite (TMP), dimethyl methylphosphonate (DMMP), and diethyl ethylphosphonate (DEEP).
[0033] Fluorinated solvents include one or more of the following: 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether (TTE), bis(2,2,2-trifluoroethyl) ether (BTFE), 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (TFTFE), methoxynonfluorobutane (MOFB), ethoxynonfluorobutane (EOFB), fluorobenzene (FB), 1,2-bis(1,1,2,2-tetrafluoroethoxy)ethane (BTFEE), and tri(trifluoroethoxy)methane (TFEO).
[0034] The ionic liquid includes 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonate)imide, 1-methyl-propylpyrrolidineonium tetrafluoroborate, 1-methyl-propylpyrrolidineonium hexafluorophosphate, 1-methyl-1-propylpyrrolidineonium bis(fluorosulfonyl)imide, and 1-methyl-1-propylpyrrolidineonium bis(trifluoro)imide. One or more of the following: methanesulfonate imide salt, N,N-diethyl-N-methyl-N-methoxyethoxyalkyl tetrafluoroborate, N,N-diethyl-N-methyl-N-methoxyethoxyalkyl bis(trifluoromethanesulfonyl)imide salt, N-butyl-N-methylpiperidine bis(trifluoromethanesulfonyl)imide salt, N-butyl-N-methylpiperidine bis(fluorosulfonyl)imide salt, 1-methyl-1-propylpiperidine bis(fluorosulfonyl)imide salt (PP13FSI), and 1-methyl-1-propylpiperidine bis(trifluoromethanesulfonyl)imide salt.
[0035] Specifically, the additives include one or more of the following: perfluorohexanone (PFHK), pentafluoroethoxycyclotriphosphazene (PFPN), ethyl hexafluorophosphate (FEP), propyl pentafluorophosphate (FPP), tris(trimethylsilane) phosphate (TMSP), 1,3-propenesulfonyl lactone (1,3-PS), lithium tetrafluoroborate (LiBF4), vinyltrimethylsilane (VTMS), vinyltriethoxysilane (VTES), tetravinylsilane (TVS), dimethyldimethoxysilane (DMMS), trimethoxyphenylsilane (TMPS), tris(pentafluorophenyl)borane (TPFPB), triethyl borate (TEB), tris(trimethylsilyl)borate (TMSB), lithium difluorophosphate (LiDFP), lithium difluorooxalate borate (LiDFOB), lithium difluorobis(oxalate) phosphate (LiDFOP), lithium nitrate (LiNO3), lithium bis(oxalate) borate (LiBOB), and trifuranyl phosphite (FuP).
[0036] In a preferred embodiment, the solvent contains at least a fluorinated solvent.
[0037] In one embodiment, the mass content of the additive in the electrolyte is 0.5% to 15%, and the mass content of the solvent in the electrolyte is 15% to 90%. Specifically, the mass content of the additive includes, but is not limited to, 0.5%, 1%, 3%, 5%, 7%, 9%, 11%, 13%, or 15%. By adjusting the content of additives and solvents in the electrolyte, the flame retardant properties of the electrolyte are improved, the stability of the electrolyte is enhanced, and the side reactions of the electrolyte are reduced, thereby improving the safety performance of the battery.
[0038] In one embodiment, both the positive electrode current collector and the negative electrode current collector comprise metal foil and / or a composite current collector. The current collector can be used alternately with either of these two types, or used individually. The composite current collector comprises a base film and conductive layers disposed on both sides of the base film. The positive electrode and the negative electrode each include a second functional layer, which is disposed on at least one surface of the metal foil and located between the corresponding active material layer and the metal foil; and / or, the second functional layer is disposed between the base film and the conductive layer. By providing the second functional layer in conjunction with the electrolyte, the local or overall temperature rise of the battery cell can be further reduced under needle penetration conditions, thus preventing thermal runaway and fire of the battery cell.
[0039] Specifically, when the electrode is a positive electrode, the metal foil is aluminum foil, and the conductive layer is metallic aluminum. When the electrode is a negative electrode, the metal foil is copper foil, and the conductive layer is one or more of copper, nickel, copper-nickel, and copper-zinc alloys.
[0040] The base film includes one or more of polyethylene, polyethylene terephthalate, polyimide, polypropylene, polyamide, polyphenylene sulfide, and polyethylene naphthalate.
[0041] In one embodiment, the second functional layer includes a strength layer and / or a safety layer; the strength layer includes an alumina layer; and the safety layer includes one or more of barium titanate, lead titanate, and polymethyl methacrylate.
[0042] When the second functional layer is a strength layer, it enhances the strength of the current collector. When the second functional layer is a safety layer, the material of the safety layer is characterized by an increase in resistance with increasing temperature, thus achieving dual protection against thermal runaway and short circuits inside the battery.
[0043] Furthermore, the second functional layer can be configured as one or more layers. When multiple second functional layers are configured, they are interspersed between the conductive layers. The second functional layer can be prepared by methods such as physical vapor deposition (PVD) or wet coating.
[0044] In one embodiment, an underlayer is provided between the base film and the second functional layer, the underlayer comprising one or more elements selected from iron, chromium, aluminum, silicon, magnesium, copper, manganese, zinc, lead, titanium, and nickel. By providing the underlayer, the adhesion between the functional layer and the base film is increased.
[0045] Specifically, when the composite current collector is a positive electrode current collector, the bottom layer contains one or more of the elements selected from iron, silicon, magnesium, copper, manganese, zinc, lead, titanium, and nickel. When the composite current collector is a negative electrode current collector, the bottom layer contains one or more of the elements selected from chromium, aluminum, magnesium, manganese, zinc, titanium, and nickel.
[0046] In some embodiments, in the positive electrode sheet, the thickness of the aluminum foil is 2~15μm, the thickness of the base film is 1~8μm, the thickness of the conductive layer is 0.2~10μm, the thickness of the second functional layer is 5~500nm, and the thickness of the underlayer is 10~1000nm. By controlling the thickness of the aluminum foil and the positive current collector in the positive electrode sheet, the quality of the positive electrode sheet can be further controlled, so as to improve the mass energy density of the battery.
[0047] In the negative electrode, the copper foil has a thickness of 2–12 μm, the base film has a thickness of 1–6 μm, the conductive layer has a thickness of 0.1–10 μm, the second functional layer has a thickness of 5–500 nm, and the underlayer has a thickness of 10–500 nm. By controlling the thickness of the aluminum foil and the positive current collector in the positive electrode, the quality of the positive electrode can be further controlled, thereby improving the mass energy density of the battery.
[0048] In one embodiment, the positive electrode further includes an electronic insulating protective layer disposed at the edge of the positive current collector, and the side of the electronic insulating protective layer closest to the positive active material layer intersects with or covers a portion of the positive active material layer. By providing the electronic insulating protective layer, lithium plating at the electrode edge and short circuits between the positive and negative electrodes are prevented.
[0049] Furthermore, the electronic insulating protective layer extends 0-20 mm towards the edge of the current collector and 0-20 mm towards the positive electrode active material layer, with the intersection of the insulating protective layer and the positive electrode active material layer as the line. The thickness is 1~40 μm.
[0050] In one embodiment, the electronic insulating protective layer comprises one or more of the following: polyvinylidene fluoride and its modified forms, polyimide and its modified forms, polytetrafluoroethylene and its modified forms, para-aramid and its modified forms, meta-aramid and its modified forms, alumina, boehmite, zinc oxide, zirconium dioxide, titanium dioxide, and barium sulfate. By selecting the above compounds, lithium deposition at the electrode edges is effectively prevented.
[0051] In one embodiment, the positive electrode active material layer includes a positive electrode material, the thermal decomposition temperature of which is 180℃-300℃ and the withstand voltage range is 0V-4.8V.
[0052] Specifically, the cathode material includes LiNi x Mn y Co z O2 (0.3≤x≤0.99, x+y+z=1), LiNi x Al y Co z O2 (0.3≤x≤0.99, x+y+z=1), lithium manganese iron phosphate (LiFe) x Mny The cathode materials include lithium iron phosphate (LiFePO4), lithium manganese oxide (LiMn2O4), lithium nickel oxide (LiNiO2), lithium-rich manganese-based (xLi2MnO3·(1-x)LiMO2, where M = one or more of Ni, Co, and Mn), lithium nickel manganese oxide (LMNO), lithium vanadium phosphate (Li3V2(PO4)3), lithium vanadium oxide phosphate (LiVOPO4), and one or more of the above-mentioned modified cathode materials. The particle size of the cathode material is 10 nm to 10 μm.
[0053] Furthermore, the cathode material contains a dopant element, which is at least one selected from Al, B, Ba, Bi, Ca, Cr, Ce, Co, Er, Ga, Ge, Ho, K, La, Mg, Mo, Na, Nb, Pd, P, Si, Sb, Sr, Se, Ru, Rh, Ta, Te, Ti, W, V, Y, Zr, and Zn; more preferably, the cathode material contains a coating element, which is at least one selected from Al, B, Ba, Bi, Ca, Cr, Ce, Co, Cl, Er, Ga, Ge, Ho, In, K, La, Mg, Mo, Na, Nb, Pd, P, Si, Sb, Sr, Se, Ru, Rh, Ta, Te, Ti, W, V, Y, Zr, and Zn. The number of coating layers is ≥1.
[0054] In one embodiment, based on the mass of the positive electrode active material layer as 100%, the positive electrode active material layer comprises the following components: 70%~99.9% positive electrode active material, 0.05%~15% electronic conductive agent, and 0.05%~15% additives. By controlling the content of each component in the positive electrode active material layer, the surface density, compaction density, porosity, thickness, and areal specific capacity of the positive electrode sheet can be adjusted, thereby improving the mass energy density and volumetric energy density of the battery.
[0055] Specifically, the length of the positive electrode sheet is 20-1000 mm and the width is 10-300 mm; The length of the positive electrode active material layer is 20~1000mm, and the width of the positive electrode active material layer is 10~300mm.
[0056] The areal density of the positive electrode sheet is 2~40 mg / cm³. 2 The compaction density of the positive electrode sheet is 1~6 mg / cm³. 3 The thickness of the positive electrode sheet is 10~300μm, the porosity is 5~50%, and the areal specific volume is 0.1~30 mAh / cm³. 2 Positive electrode sheets that meet the above conditions can achieve high areal density and high compaction density, thereby improving the battery's mass energy density and volumetric energy density.
[0057] Further, in one embodiment, the electronically conductive agent includes one or more of graphite, hard carbon, soft carbon, carbon nanotubes, graphene, porous carbon, superconducting carbon black, acetylene black, furnace black, and vapor-grown carbon fiber (VGCF). The additives include one or more of the following: polytetrafluoroethylene and its derivatives, polyvinylidene fluoride and its derivatives, silicone rubber, styrene-butadiene rubber, hydrogenated nitrile rubber, boronized polyethylene glycol, cellulose, cellulose esters, cellulose ethers, nitrocellulose, carboxyalkyl cellulose, cellulose salts, sodium carboxymethyl cellulose and cellulose salt derivatives, polyacrylic acid, polyamide, polyvinyl alcohol, polyethyleneimine, and polyimide.
[0058] The positive electrode sheet can be prepared by wet method, which involves mixing the positive active material, electronic conductive agent, additive and dispersant in a preset ratio to form a slurry, coating the obtained slurry on the current collector at a certain loading, and finally drying and rolling it at a temperature of 60℃~180℃ to form an electrode sheet.
[0059] Alternatively, a dry preparation method can be selected, in which the positive electrode active material, electronic conductive agent and additives are mixed in a preset ratio, shear force is applied to the mixed powder to make the additives fibrous, and a preform is obtained. The preform is then extruded or rolled into a self-supporting membrane with a thickness of 0~300μm.
[0060] Finally, the self-supporting film is loaded onto the current collector that rolls between two rollers, and rolled to form an electrode. The surface of this current collector can be coated with a carbon layer or conductive adhesive, with a thickness of 0~5μm.
[0061] In one embodiment, the lithium content in the negative electrode active material layer is 70-100% by mass. By limiting the lithium content, the electrochemical activity of the negative electrode is satisfied.
[0062] The length of the negative electrode sheet is 20-1500 mm, and the width of the negative electrode sheet is 10-300 mm; the length of the negative electrode active material layer is 0-1000 mm, and the width of the negative electrode active material layer is 0-300 mm. When the length or width of the negative electrode active material layer region is 0, the negative electrode sheet is a lithium-free negative electrode.
[0063] In one embodiment, the SEI layer includes one or more of a lithium compound layer, a carbon material layer, and a polymer layer; The lithium alloy layer comprises an alloy formed of metallic lithium and one or more of the following: gold, indium, magnesium, zinc, chromium, nickel, molybdenum, tungsten, vanadium, titanium, niobium, zirconium, cobalt, manganese, aluminum, copper, boron, silver, tin, silicon, carbon, phosphorus, and bismuth.
[0064] By preparing the aforementioned SEI layer and lithium alloy layer, direct contact between metallic lithium and electrolyte / electrolyte can be effectively avoided, which helps in the uniform deposition of lithium ions and their diffusion inside the lithium metal anode. This can effectively improve problems such as SEI film thickening and continuous lithium dendrite growth, thereby enhancing the safety performance of the battery cell.
[0065] In one embodiment, the lithium compound layer comprises one or more compounds formed with metallic lithium selected from fluorine, oxygen, sulfur, nitrogen, carbon, and phosphorus; The carbon material layer includes one or more of graphite, soft carbon, hard carbon, carbon black, amorphous carbon, graphene, and carbon nanotubes. The polymer layer comprises one or more of the following: polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polydimethylsiloxane, polyacrylic acid, metal-organic framework, covalent organic framework, polyether, polyester, polyurethane, polycarbonate, polyacrylate, polyacrylamide, polysiloxane, polyimide, self-porous polymer, and supramolecular polymer.
[0066] When the SEI layer is an organic-inorganic composite layer, the SEI layer is formed by uniformly combining one or more materials selected from the above-mentioned carbon material layer and lithium compound layer with one or more materials selected from the above-mentioned polymer layer.
[0067] In one embodiment, the thickness of both the SEI layer and the lithium alloy layer is 0.01~5μm, and the thickness of the negative electrode active material layer is 0.1~100μm. By adjusting the thickness of the SEI layer and the lithium alloy layer, the energy density of the battery can be increased without affecting the battery's charging and discharging, while avoiding the growth of lithium dendrites.
[0068] In one embodiment, the electrolyte further includes a lithium salt with a concentration of 0.5 to 5 M.
[0069] Specifically, the lithium salt concentration includes, but is not limited to, 0.5M, 1M, 1.2M, 1.5M, 2M, 3M, or 5M. The solvent mass content includes, but is not limited to, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or 90%.
[0070] In some embodiments, the lithium salt includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, (LiCF3SO), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bisfluorosulfonylimide (LiFSI), lithium trifluoromethanesulfonyl-perfluorobutylsulfonylimide (LiTNFSI), lithium fluorosulfonyl-perfluorobutylsulfonylimide (LiFNFSI), lithium bis(oxalateborate)borate (LiBOB), lithium difluorooxalateborate (LiDFOB), lithium difluorophosphate, and lithium nitrate.
[0071] In one embodiment, the battery further includes a separator, which is a polymer porous base membrane or a coated separator, wherein the coated separator includes a polymer porous base membrane and a functional coating disposed on at least one side of the polymer porous base membrane; The polymer porous base membrane includes at least one of polyethylene and polypropylene; the functional coating includes one or more of a high-temperature resistant compound, a polymer binder, a thickener, and a wetting agent. By using the high-temperature resistant compound in the functional coating, which has the advantages of a large specific surface area and high conductivity, high ionic conductivity is achieved, thereby reducing the mass ratio of the separator and increasing the energy density of the battery. The included polymer binder improves the adhesion between the functional coating and the polymer porous base membrane, preventing the coating from detaching when the battery is subjected to external impacts. The included wetting agent improves the wettability of the separator.
[0072] Specifically, the ratio of the tensile strength in the MD to TD directions of the polymer porous base membrane is 0.01-100. The functional coating has at least one layer and can face either the positive or negative electrode.
[0073] In one embodiment, the diaphragm has a length of 20 to 1000 mm and a width of 10 to 300 mm.
[0074] In one embodiment, the high-temperature resistant compound includes one or more of oxide solid electrolytes, halide solid electrolytes, sulfide solid electrolytes, alumina, boehmite, zinc oxide, zirconium dioxide, titanium dioxide, barium sulfate, polyvinylidene fluoride and its copolymers, aramid, polymethyl methacrylate and its modifiers.
[0075] Oxide solid electrolytes include, but are not limited to, LATP, LLZO, and LLZTO; halide solid electrolytes include, but are not limited to, Li3InCl6, Li2MnCl4, Li2ZnCl4, Li3YCl6, and Li6CoCl8; and sulfide solid electrolytes include, but are not limited to, Li3PS4 and Li7P3S. 11 , Li6PS5Cl, LSPSCl, Li4SnS4.
[0076] The polymer binder includes one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethyl methacrylate and its copolymers, polyacrylic acid and its copolymers, lithium polyacrylate, polyacrylonitrile, styrene-butadiene rubber, polyvinyl alcohol, polytetrafluoroethylene, polyacrylamide, polyvinyl acetate and polyurethane.
[0077] The thickener includes one or more of carboxymethyl cellulose, sodium alginate, terpineol, polyacrylic acid, polyvinyl alcohol, xanthan gum, gum arabic, gelatin, and guar gum.
[0078] The wetting agent includes one or more of the following: polydimethylsiloxane, polyether-modified siloxane, polyoxyethylene ether, octylphenol polyoxyethylene ether, polyether siloxane, sodium alkylbenzene sulfonate, polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, or sodium lauryl sulfate.
[0079] The separators made from the above materials have good low pore-closing temperature (10-200℃), heat shrinkage resistance (MD and TD≤30 after 1h at 130℃), puncture strength (0-1000gf) and high membrane rupture temperature (10-1000℃), thus ensuring the high safety of the battery.
[0080] Specifically, the coating diaphragm is prepared by one or more of the following methods: roller coating, spray coating, dot matrix coating, and intermittent coating, wherein the coating thickness is 0.5~5 μm, the drying temperature is 30~80 ℃, and the coating linear speed is 80~150 ms. -1 .
[0081] In one embodiment, the average particle size of the polymer binder is 0.1 to 10 μm. By using a polymer binder within this particle size range, uniformity during the application of the functional coating is ensured.
[0082] In one embodiment, the functional coating, based on 100% by mass, comprises the following components: 80%–99% high-temperature resistant compound, 0–10% wetting agent, 0–10% polymer binder, and 0–10% thickener. By adjusting the content of each component of the diaphragm, the diaphragm exhibits good heat shrinkage resistance, puncture strength, and membrane rupture temperature.
[0083] In one embodiment, the positive electrode further includes a positive current collector formed tab and a positive electrode adapter tab, wherein the positive electrode adapter tab is an aluminum metal tab; the negative electrode further includes a negative current collector formed tab and a negative electrode adapter tab, wherein the negative electrode adapter tab is a nickel metal tab or a copper-plated nickel tab.
[0084] The length of the positive current collector formed tab is 0~10mm; the width of the positive current collector formed tab is 0~300mm; and the thickness of the positive electrode adapter tab is 100~200μm.
[0085] The length of the negative electrode current collector formed tab is 0~10mm; the width of the negative electrode current collector formed tab is 0~300mm; and the thickness of the negative electrode adapter tab is 100~200μm.
[0086] Specifically, the positive or negative electrode adapter tabs can be fabricated by physical hot pressing and high-frequency hot pressing processes, respectively, to connect to the positive or negative current collector tabs. By limiting the length, width, and thickness of the tabs, the space occupied by the tabs can be reduced while ensuring the flow rate, thereby increasing the energy density.
[0087] In one embodiment, the battery has a length dimension of 20mm-1000mm, a width dimension of 10mm-300mm, and a thickness dimension of 0.2mm-50mm, with a length-to-width ratio of 1:1-10:1. The top seal of the battery may have an irregular design.
[0088] The battery has a capacity of 1~200Ah; a nominal voltage of 3.0~4.8V; a total energy of 3.0Wh~960Wh; and an operating voltage range of 2.0~5.0V.
[0089] In this embodiment, the battery has an extremely wide range of battery size, capacity, and energy. The adjustable length, width, and thickness of the battery make it compatible with battery module and battery compartment designs for various terminal carriers such as power tools, robots, aircraft, new energy vehicles, and energy storage devices, achieving lightweighting and long battery life for the equipment.
[0090] In one embodiment, the battery is encapsulated using an aluminum-plastic film, which is a multilayer composite film of nylon-aluminum layer-polypropylene (PP).
[0091] The total thickness of the aluminum-plastic film can range from 70 μm to 170 μm, and the areal density can range from 14.5 to 26.0 mg / cm². The thickness of the nylon layer can range from 15 μm to 25 μm, the thickness of the aluminum layer can range from 30 μm to 60 μm, and the thickness of the PP layer can range from 60 μm to 80 μm. By using the above-mentioned aluminum-plastic film, the battery can possess high tensile strength, high puncture resistance, and high elongation at break, ensuring that the battery maintains high safety performance even in extreme environments.
[0092] Specifically, the battery is manufactured as follows: 1. The positive electrode, the negative electrode, and the separator are stacked together to obtain a semi-finished stacked battery.
[0093] 2. Weld the positive and negative current collector tabs of the semi-finished stacked battery from step 1 to the transfer welding tabs, and then encapsulate them into the aluminum-plastic film to obtain the semi-finished battery.
[0094] 3. After adding the semi-finished battery from step 2 to the electrolyte, the battery is subjected to vacuum settling, formation, and degassing, and then the aluminum-plastic film is re-encapsulated to obtain the battery.
[0095] Specifically, the aluminum-plastic film is a multi-layer composite film composed of nylon, aluminum layer, and polypropylene (PP).
[0096] The thickness of the aluminum-plastic film can be 80μm-160μm.
[0097] The aluminum-plastic film is prepared by either a dry method or a hot method. The dry method involves bonding nylon, aluminum, and PP with an adhesive and then directly pressing them together. The hot method involves bonding nylon, aluminum, and polypropylene with microporous foamed polypropylene (MPP) and then slowly heating and pressing them together.
[0098] It should be noted that in the battery, the negative electrode has one more layer than the positive electrode. That is, the outermost layer of the semi-finished stacked battery is a negative electrode sheet, and the outermost negative electrode sheet can be a single-sided active material, with the surface not opposite to the positive electrode sheet using an empty current collector; or, the outermost negative electrode sheet can also be a double-sided active material.
[0099] An embodiment of the present invention also provides an electrical device, including the aforementioned battery.
[0100] The present invention will be further illustrated by the following examples.
[0101] Example 1 This embodiment illustrates the battery disclosed in this invention and includes the following operational steps: Electrolyte: Dimethyl ethylene glycol ether (DME), 1,2-bis(1,1,2,2-tetrafluoroethoxy)ethane (BTFEE), and 1-methyl-1-propylpyrrolidineonium bis(fluorosulfonyl)imide (Pyr13FSI) were mixed in a volume ratio of 1:1:0.01. Then, trimethoxyphenylsilane (TMPS) and LiFSI were added. The mass content of trimethoxyphenylsilane (TMPS) in the electrolyte was 0.5%, and the lithium salt concentration was 1.5M.
[0102] Battery manufacturing Preparation of positive electrode sheet The surface of the positive electrode current collector is coated with an aluminum oxide layer and a barium titanate layer in sequence.
[0103] Take the positive electrode active material Li according to a mass ratio of 93:4:3 1.03 Ni0.915 Co 0.045 Mn 0.035 Zr 0.005 O2, conductive carbon black Super-P, and binder polyvinylidene fluoride (PVDF) are mixed and then dispersed in an appropriate amount of N-methyl-2-pyrrolidone (NMP) to obtain the positive electrode slurry. The resulting slurry is then uniformly coated on both sides of the positive electrode current collector.
[0104] An alumina layer is coated on the edge of the positive current collector, and after drying, rolling, and vacuum drying, aluminum leads are welded on using an ultrasonic welder to obtain the positive electrode sheet. The thickness of the positive electrode sheet is 400 μm. The length of the positive electrode sheet is 680 mm, and the width of the positive electrode sheet is 162 mm. The length of the positive active material layer is 680 mm, the width of the positive active material layer is 162 mm, and the thickness of the positive electrode sheet is 400 μm.
[0105] Preparation of negative electrode sheet The negative electrode uses a lithium metal negative electrode, and an SEI layer containing lithium fluoride and lithium nitride is formed on the surface of the lithium metal through physical vapor deposition, with a thickness of 1 μm.
[0106] The negative electrode has a length of 683 mm, a width of 164 mm, and a thickness of 45 μm.
[0107] Preparation of diaphragm Boehmite, PAA, carboxymethyl cellulose, and polydimethylsiloxane were mixed in a mass ratio of 86:5:3:6 to prepare a slurry. The slurry was then roller-coated onto both sides of a polyethylene film and dried to obtain a coated diaphragm.
[0108] Cell manufacturing A coated separator with a thickness of 20 μm is placed between the positive and negative electrode sheets prepared above. Then, the sandwich structure composed of the positive electrode sheet, negative electrode sheet and separator is stacked and packaged with aluminum-plastic film to produce a soft-pack battery cell with a capacity of 1Ah ready for liquid injection.
[0109] The battery is obtained by injecting electrolyte and forming the cells.
[0110] The battery is 700mm long, 180mm wide, and 28mm thick.
[0111] Examples 2-8 Examples 2-8 illustrate the battery disclosed in this invention, including most of the operating steps in Example 1 above, except that the formulation in Table 1 is used.
[0112] Table 1 Examples 9-14 Examples 9-14 illustrate the battery disclosed in this invention, including most of the operating steps in Example 1 above, except that the formulation in Table 2 is used.
[0113] Table 2 Examples 15-19 Examples 15-19 illustrate the battery disclosed in this invention, including most of the operating steps in Example 1 above, except that the formulation in Table 3 is used.
[0114] Table 3 Comparative Examples 1-2 Comparative Examples 1-2 are used to illustrate the battery disclosed in this invention, including most of the operating steps in Example 1, except that they use the formulation in Table 1.
[0115] Performance testing I. The following performance tests were performed on the batteries obtained in the above embodiments and comparative examples: (1) Electrolyte-cathode thermal stability test: After the battery is disassembled, the electrolyte-wetted cathode sheet is tested by differential scanning calorimetry (DSC). By observing the endothermic and exothermic reactions of the electrolyte-cathode composite system under high temperature conditions, its thermal stability is analyzed. The test is carried out in a nitrogen atmosphere. The test temperature range is 30℃~300℃, the heating rate is 5℃ / min, and the cooling rate is 10℃ / min.
[0116] (2) Flame retardancy test of electrolyte: After disassembling the battery, collect the electrolyte, immerse a spherical glass fiber cotton core (about 1 cm in diameter) in the electrolyte, take it out, drain it, weigh it, calculate the amount of liquid absorbed by the cotton ball, and ignite the cotton ball after absorbing the liquid with a spray gun. Use a stopwatch to record the burning time of the cotton ball after removing the spray gun, and calculate the self-extinguishing time.
[0117] (3) Needle penetration performance test: 1. Charge the individual battery cells to the cutoff voltage according to the standard charging procedure; 2. Needle penetration process requirements: a) Needle material: steel; b) Needle diameter: 3 mm~8 mm; c) Needle tip shape: conical, angle 20°~60°; d) Needle penetration speed: 0.1 mm / s~1 mm / s; e) Needle penetration position and direction: perpendicular to the electrode; f) Needle penetration stopping condition: until thermal runaway, or until the needle penetration depth reaches 90% of the trigger cell. 3. Standby: 1 h. Judgment criteria: The battery should not catch fire or explode.
[0118] (4) Cyclic performance test: The battery was subjected to a 25°C, 0.2C / 0.5D cyclic charge-discharge test within a voltage range of 3.0V~4.4V, and the capacity retention rate after 100 cycles was recorded.
[0119] (5) Hot chamber test: The test object is a single battery cell. The battery cell is charged to the charging cut-off capacity and then placed in the hot chamber. The hot chamber parameters are as follows: 1. Heating rate: 5℃ / min ± 2℃ / min; 2. Heating temperature: 130℃ ± 2℃ and then held at the temperature for 30min; 3. Heating time: 30min. The judgment criteria are that the battery does not catch fire or explode.
[0120] The test results are shown in Table 4.
[0121] Table 4 As shown in the test results of Examples 1-8 and Comparative Examples 1 and 2, by optimizing the solvent and additive system in this application, the thermal stability and antioxidant capacity of the electrolyte can be effectively improved, the risk of high-temperature volatilization and decomposition can be reduced, the battery safety performance can be improved, and at the same time, the reduction gas generation and dendrite growth at the negative electrode interface can be suppressed, thereby improving the cycle performance of the battery. As shown in the test results of Examples 1 and 15-19, when the first functional layer is not set, the battery cannot pass the hot box test.
[0122] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A battery, characterized in that, The device includes an electrolyte, a positive electrode, and a negative electrode. The electrolyte includes additives and a solvent. The additives include one or more of the following: silanes and their derivatives, fluorinated compounds, phosphazene compounds, ethyl hexafluorophosphate, propyl pentafluorophosphate, tris(trimethylsilane) phosphate, trifuranyl phosphite, and boron-containing compounds. The solvent includes one or more of carbonate solvents, ether solvents, phosphate solvents, fluorinated solvents, and ionic liquids; The positive electrode sheet includes a positive current collector and a positive active material layer, wherein the positive active material layer is disposed on at least one surface of the positive current collector; The negative electrode sheet includes a negative current collector, a negative active material layer, and a first functional layer. The negative active material layer includes metallic lithium or a lithium alloy and is disposed on at least one surface of the negative current collector. The first functional layer is disposed on the side of the negative active material layer opposite to the negative current collector and includes an SEI layer and / or a lithium alloy layer.
2. The battery according to claim 1, characterized in that, The silanes and their derivatives include one or more of vinyltrimethylsilane, tetravinylsilane, dimethyldimethoxysilane, and trimethoxyphenylsilane; And / or, the fluorinated compound includes perfluorohexanone; And / or, the phosphazene compounds include pentafluoroethoxycyclotriphosphazene; And / or, the boron-containing compound includes one or more of tris(pentafluorophenyl)borane, triethyl borate, and tris(trimethylsilyl)borate.
3. The battery according to claim 1, characterized in that, The additives also include one or more of 1,3-propenesulfonate lactone, lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorooxalate borate, and lithium difluorobis(oxalate) phosphate.
4. The battery according to claim 1, characterized in that, The additive in the electrolyte has a mass content of 0.5% to 15%, and the solvent in the electrolyte has a mass content of 15% to 90%.
5. The battery according to claim 1, characterized in that, Both the positive electrode current collector and the negative electrode current collector include metal foil and / or composite current collector; the composite current collector includes a base film and conductive layers disposed on both sides of the base film; The positive electrode and the negative electrode further include a second functional layer, which is disposed on at least one surface of the metal foil; and / or, the second functional layer is disposed between the base film and the conductive layer.
6. The battery according to claim 5, characterized in that, The second functional layer includes a strength layer and / or a security layer; The strength layer includes an aluminum oxide layer; the safety layer includes one or more of barium titanate, lead titanate, and polymethyl methacrylate.
7. The battery according to claim 5, characterized in that, An underlayer is provided between the base film and the second functional layer, and the underlayer includes one or more of the following elements: iron, silicon, magnesium, copper, manganese, zinc, lead, titanium, chromium, aluminum, and nickel.
8. The battery according to claim 1, characterized in that, The positive electrode sheet also includes an electronic insulation protective layer, which is disposed at the edge of the positive current collector, and the side of the electronic insulation protective layer close to the positive active material layer intersects with or covers part of the positive active material layer.
9. The battery according to claim 8, characterized in that, The electronic insulating protective layer includes one or more of the following: polyvinylidene fluoride and its modified forms, polyimide and its modified forms, polytetrafluoroethylene and its modified forms, para-aramid and its modified forms, meta-aramid and its modified forms, alumina, boehmite, zinc oxide, zirconium dioxide, titanium dioxide, and barium sulfate.
10. The battery according to claim 1, characterized in that, The SEI layer includes one or more of the following: a lithium compound layer, a carbon material layer, and a polymer layer; The lithium alloy layer comprises an alloy formed of metallic lithium and one or more of the following: gold, indium, magnesium, zinc, chromium, nickel, molybdenum, tungsten, vanadium, titanium, niobium, zirconium, cobalt, manganese, aluminum, copper, boron, silver, tin, silicon, carbon, phosphorus, and bismuth.
11. The battery according to claim 1, characterized in that, The electrolyte also includes a lithium salt, the concentration of which is 0.5~5M.
12. The battery according to claim 1, characterized in that, The battery also includes a separator, which is a polymer porous base membrane or a coated separator. The coated separator includes a polymer porous base membrane and a functional coating disposed on at least one side of the polymer porous base membrane. The polymer porous base membrane includes at least one of polyethylene and polypropylene; the functional coating includes one or more of a high-temperature resistant compound, a polymer binder, a thickener, and a wetting agent.
13. The battery according to claim 12, characterized in that, The high-temperature resistant compounds include one or more of the following: oxide solid electrolytes, halide solid electrolytes, sulfide solid electrolytes, alumina, boehmite, zinc oxide, zirconium dioxide, titanium dioxide, barium sulfate, polyvinylidene fluoride and its copolymers, aramid, polymethyl methacrylate and its modifiers.
14. An electrical appliance, characterized in that, Includes the battery as described in any one of claims 1 to 13.